Spinach-based fluorescent light-up biosensors for multiplexed and label-free detection of microRNAs. Issue 24 (7th March 2018) - Ying, Zhan-Ming; Tu, Bin; Liu, Lan; Tang, Hao; Tang, Li-Juan; Jiang, Jian-Hui
Abstract : A novel Spinach-based fluorescent light-up biosensor utilizing the T7 in vitro transcription process to generate unmodified Spinach sequences for multiplexed microRNA detection has been developed. Abstract : A novel Spinach-based fluorescent light-up biosensor utilizing the T7 in vitro transcription process to generate unmodified Spinach sequences for multiplexed microRNA detection has been developed.